Croton sp.: a review about Popular Uses, Biological Activities and Chemical Composition (Research, Society and Development, 2022)
The genus Croton, belonging to the Euphorbiaceae family, is a plant with shrubby characteristics, with the ability to regrow in times of rain, develops wildly, especially in deforestation areas, being reported mainly in the Caatinga and Forest region. One of the main characteristics of this genus is that several species are rich in chemical constituents of importance for medicine. In this way, this review of the literature, has an objective that findings regarding the biological activities and chemical composition of Croton species. This study is a literature review, carried out in the following databases: SciELO, BVS, MEDLINE, LILACS, PubMed and ScienceDirect, with a time frame between 1997 and 2020. The articles studied have shown different activities for Croton species, such as anti-inflammatory, antihypertensive, antifungal, antimicrobial, antidiabetic, antioxidant, antinociceptive and anti-tumor. Regarding toxicological aspects, the findings suggest caution in the use of Croton species, as some are toxic. While, regarding the chemical composition, in most species the presence of several secondary metabolites is observed, such as alkaloids, terpenoids, flavonoids and other phenolic compounds. Therefore, the results described in this article suggest that the therapeutic application of Croton species is supported by the literature, however we point out that caution is required in the use of Croton species, some present due to toxicity.